1999
DOI: 10.1021/jp983878+
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Lewis Acid Sites of Aluminum-Modified Silica. A Theoretical and Experimental Study

Abstract: The structures and relative Lewis acidities of the catalytic sites of four aluminum-modified silicas have been studied by means of theoretical calculations on model compounds, as well as by spectroscopic and catalytic experiments. Theoretical calculations indicate that the silica treated with Et2AlCl has aluminum sites that are more acidic than those of AlCl3. The thermic treatment of the aluminum-modified silicas leads to the appearance of new, very strong acidic sites, as shown by infrared and reactivity exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…On the other hand, when the silica is treated with Et 2 AlCl, attachment of the Al onto the surface through reaction of the silanol groups and displacement of the alkyl and/or chlorine groups takes place. A recent theoretical and experimental study [26] has shown that the acidity of the resulting aluminum centers is at least as high as, if not superior to, that of aluminum trichloride. We therefore decided to use two simple models for the Lewis acid, namely the molecules of ZnCl 2 and AlCl 3 coordinated to the corresponding cycloadducts.…”
Section: Computational Resultsmentioning
confidence: 99%
“…On the other hand, when the silica is treated with Et 2 AlCl, attachment of the Al onto the surface through reaction of the silanol groups and displacement of the alkyl and/or chlorine groups takes place. A recent theoretical and experimental study [26] has shown that the acidity of the resulting aluminum centers is at least as high as, if not superior to, that of aluminum trichloride. We therefore decided to use two simple models for the Lewis acid, namely the molecules of ZnCl 2 and AlCl 3 coordinated to the corresponding cycloadducts.…”
Section: Computational Resultsmentioning
confidence: 99%
“…A similar increase in Lewis acidity was observed in the case of Al-supported Lewis acids. 24 Interestingly, only the non-ordered silica-supported catalysts are able to promote the epoxide opening with water, whereas mesostructured supports are selective towards the opening with tert-butanol. The hydrophilic/hydrophobic balance and the more probable presence of different titanium species (mono-, di-, and tripodal) on silica may account for those results.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…Conversion represents the efficiency of the epoxidation reaction, whereas the selectivity to styrene oxide depends on the activity of the catalyst for rearrangement to phenyl acetaldehyde. As can be seen in Table 2, should produce a larger amount of monopodal sites (Figure 1), whose acidity [36] and hence the activity for epoxidation [16] must be lower than the bipodal and tripodal sites due to the lack of geometrical constrains. The catalysts based on MCM550 were recovered from the reaction mixture by simple filtration, and they were reused after washing with dichloromethane.…”
Section: Methodsmentioning
confidence: 99%